Supercritical CO2 extraction of Aurantiochytrium sp. biomass for the enhanced recovery of omega-3 fatty acids and phenolic compounds. Issue 38 (May 2020) - de Melo, M.M.R.; Sapatinha, M.; Pinheiro, J.; Lemos, M.F.L.; Bandarra, N.M.; Batista, I.; Paulo, M.C.; Coutinho, J.; Saraiva, J.A.; Portugal, I.; Silva, C.M.
Highlights: SFE of microalgae Aurantiochytrium sp. and Soxhlet extraction (n-hexane & dichloromethane). Maximization of total extraction yield, DHA & total phenolics content, & antioxidant capacity. Design of experiments with 3 factors and 2 levels (200−300 bar, 40−80 °C, 6–12 g C O 2   m i n - 1 ). Obtained DHA content 3.5-fold richer than fish oil, and 7.9-fold richer than other microalgaes. Abstract: The microalgae Aurantiochytrium sp. is a strong alternative source of ω-3 fatty acids, including docosahexaenoic acid (DHA). This work encompasses the optimization of SFE conditions to maximize the total extraction yield η T o t a l, DHA content ( C D H A ), total phenolics content ( T P C ), and antioxidant capacity ( A O C ) of the extracts produced from Aurantiochytrium sp. biomass. A full factorial experimental plan was performed, comprising three factors (pressure, temperature, and flow rate) and two levels (200−300 bar, 40−80 °C, and 6–12 g   m i n - 1, respectively). The maximum and minimum experimental results were η T o t a l =   2.1 and 13.4 wt.%, C D H A = 27.3 and 39.3 wt.%, T P C  = 1.19 and 2.24 m g G A E   g e x t r a c t - 1, and   A O C = 0.3 and 1.4 m g T E A C   g e x t r a c t - 1 . Under the studied experimental conditions, increasing pressure up to 300 bar is the optimum to rise both η T o t a l and C D H A . Temperature increase from 40 to 80 °C leads to opposing effects: it favors the concentration of phenolics in the supercritical extracts at the expenses of decreasing DHA content and total yield. Surface models were adjusted to η T o t a l, C D H A and T P C data, and the goodness of the fits ranged from coefficients of determination of 0.752-0.711 ( T P C ) to 0.997-0.994 ( C D H A ). Under optimized conditions, supercritical extracts exhibited a DHA content more than 3.5-fold richer than fish oil, and 7.9-fold richer than the best alternative microalgae species ( Pavlova lutheri ) found in the literature.